Progress in Flight Physics 2017
DOI: 10.1051/eucass/2016090173
|View full text |Cite
|
Sign up to set email alerts
|

In-flight icing on unmanned aerial vehicle and its aerodynamic penalties

Abstract: A numerical prediction of ice accretion on HQ309, SD7032, and SD7037 airfoils and its aerodynamic penalties is described. Ice accretion prediction on a three-dimensional (3D) swept wing is also presented. In addition to air §ow and drop trajectory solvers, NRC£s (National Research Council) original, 3D, morphogenetic icing modeling approach has been used. The analysis was performed for a wide range of icing conditions identi¦ed in the FAA (Federal Aviation Administration) Appendix C icing envelope. They cover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Studies on UAVs have shown that the Reynolds number has a significant influence on the physics of ice accretion and also on the subsequent aerodynamic performance penalties [16][17][18]. Icing on UAVs is similar to icing on manned aircraft with some key differences related to airframe size, mission profiles, and icing sensitivity [19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on UAVs have shown that the Reynolds number has a significant influence on the physics of ice accretion and also on the subsequent aerodynamic performance penalties [16][17][18]. Icing on UAVs is similar to icing on manned aircraft with some key differences related to airframe size, mission profiles, and icing sensitivity [19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, three-dimensional icing simulations for a wing and airfoil have been performed using icing models. To examine the effect of icing on the lift and drag forces, some researchers performed icing simulations for a swept wing under rime and glaze ice accretion conditions [4] and for an unmanned aerial vehicle [5]. Shen et al [6] performed a three-dimensional numerical simulation to reproduce the ice accretion on the engine inlet.…”
Section: Introductionmentioning
confidence: 99%
“…This study was closely related to previous work conducted at the Norwegian University of Science and Technology (NTNU) on similar topics, such as the comparison of two numerical codes for icing penalties (Hann, 2018), the effect of meteorological conditions on performance (Fajt et al , 2019), experimental ice accretion results (Hann, 2019) and experimental icing performance degradation studies (Hann et al , 2020). Further relevant work on icing performance degradation on UAV airfoils has been conducted by Williams et al (2017) and Szilder and Yuan (2017) – none of which take the effect of varying airspeeds or chord lengths into closer account.…”
Section: Introductionmentioning
confidence: 99%